2015
DOI: 10.1103/physrevapplied.4.034006
|View full text |Cite
|
Sign up to set email alerts
|

Drift-Diffusion Modeling of the Effects of Structural Disorder and Carrier Mobility on the Performance of Organic Photovoltaic Devices

Abstract: We probe the effects of structural disorder on the performance of organic photovoltaic (OPV) devices via Drift-Diffusion (D-D) modeling. We utilize ensembles of spatially disordered 1-dimensional mobility profiles to approximate the 3-dimensional structural disorder present in actual devices. Each replica in our ensemble approximates one high-conductivity pathway through the threedimensional network(s) present in a polymer-based bulk heterojunction solar cell, so that the ensemble-averaged behavior provides a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 55 publications
(77 reference statements)
1
9
0
Order By: Relevance
“…We also show in the SI the correlation of relative fraction crystallinity with other device performance figures of merit, including the short-circuit current, open-circuit voltage, and fill factor. We find that the relative fraction of crystallinity does not affect the open-circuit voltage of the devices, a result consistent with drift–diffusion simulations that have shown that V OC is relatively impervious to disorder and local environment . Instead, the correlation between relative crystalline fraction and device efficiency comes about because of correlation with both the short-circuit current and fill factor.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…We also show in the SI the correlation of relative fraction crystallinity with other device performance figures of merit, including the short-circuit current, open-circuit voltage, and fill factor. We find that the relative fraction of crystallinity does not affect the open-circuit voltage of the devices, a result consistent with drift–diffusion simulations that have shown that V OC is relatively impervious to disorder and local environment . Instead, the correlation between relative crystalline fraction and device efficiency comes about because of correlation with both the short-circuit current and fill factor.…”
Section: Resultssupporting
confidence: 86%
“…67 We also show in the SI the correlation of relative fraction crystallinity with other device performance figures of merit, including the short-circuit current, open-circuit voltage, and fill factor. We find that the 68 Instead, the correlation between relative crystalline fraction and device efficiency comes about because of correlation with both the short-circuit current and fill factor. C. Swelling Studies of Pure RBO x Films.…”
Section: ■ Results and Discussionmentioning
confidence: 79%
“…(2,3,4,6) numerically many types of macroscopic quantities for a working device can be calculated. The details for device model implementation are elaborated in numerous literatures and thus are omitted here [32][33][34] . In our simulation, initially the Onsager-Braun theory is incorporate into the model to account for the temperature variation of the CT state dissociation (or charge generation) rate, which can be written as 33,35…”
Section: Device Model Methodsmentioning
confidence: 99%
“…The relative non-dependence of an OPV device's V OC on active layer morphological features, such as the presence of a mixed-phase, is in line with our previous work that showed little effect of structural disorder on the device open circuit voltage. [34] IV. CONCLUSIONS With this study we have illustrated that the mixedcomposition phase can have both beneficial and detrimental effects on the overall performance of polymer/fullerene BHJ photovoltaic devices.…”
Section: Open-circuit Voltage (Voc)mentioning
confidence: 99%
“…[30,31] Other groups have focused on the impact of structural disorder and morphological features by performing 2-D drift-diffusion simulations to study the effects of phase separation and component arrangement on device performance [26,28,29,32,33]; we also have presented a 1-D method for examining structural disorder based on D-D simulations of ensembles of 1-D devices with position-dependent mobility profiles. [34] In this study, we present a set of 2-D drift-diffusion simulations specifically designed to probe the effects of the presence of a controllably varied mixed-composition, interfacial phase on device performance. We begin by utilizing morphologies generated by Cahn-Hilliard (C-H) modeling of binary fluid phase separation, as has been employed successfully in previous 2-D D-D modeling studies of OPVs.…”
Section: Introductionmentioning
confidence: 99%